Abjection of the female body in The Cutting Room and The Bullet Trick : the contemporanization of the patriarchal system - Tregnaghi, Gisela Leylén (2014)
The aim of this thesis is to discuss two of the works written by Louise Welsh, The Cutting Room (2002) and The Bullet Trick (2006), using Gothic and feminist criticism in order to back my hypothesis that the depiction of female bodies as abjects that the author makes in these novels has a direct correlation with current mechanisms, such as pornography, prostitution and sex trafficking, which result in the contemporanization of the patriarchal system in our culture. In other words, the novels refer to normalized cultural practices through which the apparently uprooted patriarchal order has managed to perpetuate its control over women. The first two chapters are devoted to the exploration of the theoretical framework. The thesis starts with a brief account of the historical relationship that Patriarchy has had with the female body, and then, after defining the concept of abjection, which is later utilized to refer to the treatment of the female body in our sexualized society, it presents the current state of affairs and divergent feminist views regarding this topic. The second chapter, which deals with the Gothic and its conventions, explores concepts related to the genre, such as its founding myth, male Gothic and female Gothic, and attempts to provide revised, more thorough definitions of such terms. Then, using this framework we embark in the critical analysis of the corpus which allows us to support our initial claim that the current instances of female bodily abjection are instrumental in perpetuating patriarchal power and, at the same time, to uphold the validity of the long-contested female Gothic as a critical category.